Green Synthesis Of Iron Nanoparticles From Moringa Oleifera Leaf Extracts: Characterization And Application For Diesel Range Organics And Nitrate Removal - Chima, Ubah Promise (2022)
Ethanolic extract (EtOH-MOL) and water extract (H2O-MOL) of Moringa Oleifera (M. Oleifera) plant leaves were used in this study for the biosynthesized iron nanoparticles (BINPs). M. Oleifera is a non-toxic tropical plant known for its medicinal properties and good antioxidant content. Iron sulphate heptahydrate was used as the metal precursor for the formulation of BINPs.